Rapid and robust transgenic high-grade glioma mouse models for therapy intervention studies - de Vries, Nienke A; Bruggeman, Sophia W; Hulsman, Danielle; de Vries, Hilda I; Zevenhoven, John; Buckle, Tessa; Hamans, Bob C; Leenders, William P; Beijnen, Jos H; van Lohuizen, Maarten; Berns, Anton J M; van Tellingen, Olaf (Clinical cancer research, 2010)
To develop a transgenic mouse model of glioma that can be conveniently used for testing therapy intervention strategies. High-grade glioma is a devastating and uniformly fatal disease for which better therapy is urgently needed. Typical for high-grade glioma is that glioma cells infiltrate extensively into surrounding pivotal brain structures, thereby rendering current treatments largely ineffective. Evaluation of novel therapies requires the availability of appropriate glioma mouse models. High-grade gliomas were induced by stereotactic intracranial injection of lentiviral GFAP-Cre or CMV-Cre vectors into compound LoxP-conditional mice, resulting in K-Ras(v12) expression and loss of p16(Ink4a)/p19(Arf) with or without concomitant loss of p53 or Pten. Tumors reproduced many of the features that are characteristic for human high-grade gliomas, including invasiveness and blood-brain barrier functionality. Especially, CMV-Cre injection into p53;Ink4a/Arf;K-Ras(v12) mice resulted in high-grade glioma with a short tumor latency (2-3 weeks) and full penetrance. Early detection and follow-up was accomplished by noninvasive bioluminescence imaging, and the practical utility for therapy intervention was shown in a study with temozolomide. We have developed a realistic high-grade glioma model that can be used with almost the same convenience as traditional xenograft models, thus allowing its implementation at the forefront of preclinical evaluation of new treatments.